2018
DOI: 10.1080/08927014.2018.1472244
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility ofCandida glabratabiofilms to echinocandins: alterations in the matrix composition

Abstract: Candidiases are the most recurrent fungal infections, especially among immunosuppressed patients. Although Candida albicans is still the most widespread isolated species, non-Candida albicans Candida species have been increasing. The goal of this work was to determine the susceptibility of C. glabrata biofilms to echinocandins and to evaluate their effect on the biofilm matrix composition, comparing the results with other Candida species. Drug susceptibilities were assessed through the determination of minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 72 publications
4
32
0
Order By: Relevance
“…However, that of C. glabrata seemed to increase from 0% to 12.3% during the past two decades. In addition, caspofungin shows a higher biomass reduction capacity compared with micafungin, implying that caspofungin might be superior to micafungin in treating biofilm‐forming fungi.…”
Section: Discussionmentioning
confidence: 99%
“…However, that of C. glabrata seemed to increase from 0% to 12.3% during the past two decades. In addition, caspofungin shows a higher biomass reduction capacity compared with micafungin, implying that caspofungin might be superior to micafungin in treating biofilm‐forming fungi.…”
Section: Discussionmentioning
confidence: 99%
“…On average, the oral isolates of C. glabrata were considered strong biofilm producers, whereas C. albicans (the most common species) and C. tropicalis were moderate producers. This might be because C. glabrata has been shown to have a higher aggressiveness, producing a great quantity of biofilm matrices yet also increasing chitin concentrations in the cell walls [125,126,127].…”
Section: Candidiasis and Dmmentioning
confidence: 99%
“…We have shown that treatment of colonized mice with a combination of caspofungin and the chitin synthase inhibitor Nikkomycin Z caused an increase in killing of C. glabrata within the murine GI tract and a decrease of dissemination upon immunosuppression [ 30 ]. In addition to the apparent compensation for β-glucan loss, recent studies have also noted the elevated expression of specific genes (e.g., BGL2 , XOG1 , GAS2 ) that are related to the replacement of β-1,3-glucans in the biofilm matrix following echinocandin exposure [ 54 , 55 ], which may also influence adaptation.…”
Section: Evolution Of Echinocandin Resistancementioning
confidence: 99%